Effect of Tempering Temperature on Microstructure and Mechanical Properties of High Co-Ni Secondary Hardening Steel - Pang Xuedong, Liang Xiaodong, Sun Yong, Zhai Yujia, Wen Bo, Xin Zhenfei, Li Jianxin, Wang Rui, Yan Xiaohong (Teshugang)
The effects of tempering at 380 ℃- 620 ℃ on the microstructure and mechanical properties of the double-vacuum smelting secondary hardening steel were studied by optical microscope （OM）， scanning electron microscope （SEM）， X-ray diffractometer （XRD） and tensile test. The test results showed that when tempering at 380 ℃-620 ℃， the matrix of the test steel changes from tempered lath martensite to tempered sorbite with the tempering temperature increasing， while the austenite increases. The tensile strength and yield strength reached their peak value at 440 ℃， which may be related to the increase of the strength of the test steel caused by the precipitation of Fe3C during tempering. The tensile strength and yield strength gradually decreased when tempering at 440 ℃-620 ℃. Elongation and section shrinkage gradually increased. In addition， the fracture form of impact fracture changes from quasi-cleavage fracture to ductile fracture + quasi-cleavage fracture. The comprehensive test results showed that the test steel has the best mechanical properties when tempered at 496 ℃， and can achieve better strength and toughness matching.